2011
DOI: 10.1007/s10863-011-9393-0
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dysfunction in familial amyotrophic lateral sclerosis

Abstract: A growing body of evidence suggests that mitochondrial dysfunctions play a crucial role in the pathogenesis of various neurodegenerative disorders, including amyotrophic lateral sclerosis (ALS), a neurodegenerative disease affecting both upper and lower motor neurons. Although ALS is predominantly a sporadic disease, approximately 10% of cases are familial. The most frequent familial form is caused by mutations in the gene encoding Cu/Zn superoxide dismutase 1 (SOD1). A dominant toxic gain of function of mutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 59 publications
2
23
0
Order By: Relevance
“…This is consistent with evidence of mitochondrial dysfunction in ALS (reviewed in 35 ). However, while mitochondrial function has been investigated in familial ALS with SOD1 mutations, energy metabolism in sporadic ALS (sALS) is largely unexplored.…”
Section: Introductionsupporting
confidence: 89%
“…This is consistent with evidence of mitochondrial dysfunction in ALS (reviewed in 35 ). However, while mitochondrial function has been investigated in familial ALS with SOD1 mutations, energy metabolism in sporadic ALS (sALS) is largely unexplored.…”
Section: Introductionsupporting
confidence: 89%
“…Mitochondrial dysfunction has been identified as one of the earliest defects in motor neurons of transgenic SOD1 mice and it has been suggested that mitochondrial dysfunction may play a pivotal role in motor neuron degeneration in ALS (39). We therefore analysed the mitochondrial membrane potential (Δ ψ m ) of embryonic motor neurons.…”
Section: Resultsmentioning
confidence: 99%
“…[62][63][64]76 Additionally, cellular concentrations of oxidized glutathione are expected to rise as a result of mounting oxidative stress, possibly leading to glutathionylation of SOD1 at C111 -a posttranslational modification detected previously in SOD1 from human erythrocytes and found to destabilize the SOD1 dimer. 77,78 Computational simulations have suggested that dimer dissociation, which is expected to contribute to monomer destabilization, may occur via an intermediate stabilized by glutathionylation of C111, though the fact that this intermediate could be observed in the short time frame of these simulations (approximately 100 ns) makes it highly improbable that this species is equivalent to any of the long-lived intermediates observed in the present study.…”
Section: Discussionmentioning
confidence: 96%